Degradation of VOC´s by a two stage thermal and high frequency DBDC system - Godoy-Cabrera, O.G. (Materiali in tehnologije, 2006)
The design and construction of a packed-bed thermal reactor and a high frequency operated Dielectric Barrier Discharge Cell (DBCD) based dual system conceived to carry out the degradation of hazardous organic compounds both in liquid and gaseous phases are described. The main components of this system are: i) Thermal treatment system, ii) DBCD, and iii) Specifically developed high frequency (100 kHz) resonant inverter. The power consumed by the cell during the discharges was determined, theoretically and experimentally, through Manley´s method. Using this dual system, along with gas chromatography diagnostics, high degradation efficiencies of test compounds such as toluene, benzene and carbon tetrachloride have been achieved which reach 99.976 %, 99.946 % and 99.998 %, respectively.
Keywords: razgradnja; organske snovi; visokofrekvenčni sistem; razelektritev